Cornerstones of CRISPR-Cas in drug development and therapy - Fellmann, Christof (Nat Rev Drug Discov, 2016)
The recent development of CRISPR-Cas systems as easily accessible and programmable tools for genome editing and regulation is spurring a revolution in biology. Paired with the rapid expansion of personalized and reference genomic sequence information, technologies based on CRISPR-Cas are enabling nearly unlimited genetic manipulation even in previously difficult contexts, including human cells. Although much attention has focused on the potential of CRISPR-Cas to cure Mendelian diseases, the technology also holds promise to transform the development of therapies to treat complex heritable and somatic disorders. Here we discuss how CRISPR-Cas can impact the next generation of drugs through accelerating the identification and validation of high-value targets, uncovering high confidence biomarkers and developing differentiated breakthrough therapies. We focus on the promises, pitfalls and hurdles of this revolutionary gene editing technology, and also discuss key aspects of different CRISPR-Cas screening platforms and offer our perspectives on the best practices in genome engineering.